Additional evaluation strategies in a distance university: are they alternative or complementary to written tests? - Andrés Jimenez, Carmen (2017)
Alternative evaluation strategies, such as portfolios, case studies and projects, are increasingly used instead of the traditional written tests. In this study, 307 academical orientations offered by the Exact and Natural Sciences Faculty (ECEN) at UNED, Costa Rica, during 2015, were reviewed to determine the most common type of evaluative strategy that is being used, what kind of instructions are provided, and “summative evaluation” criteria used. We also surveyed ECEN chiefs regarding evaluation alternative strategies and written tests. In 2015 written tests were used less frequently (Student T, p ≤ 0,0001) than alternative strategies such as projects, tours and laboratory reports, discussion forums and case studies. Teachers believe that alternative evaluations, combined with written tests, are the best option for their courses.